Risk of acute ischemic stroke with early versus late initiation of mechanical circulatory support in hospitalizations with acute myocardial infarction complicated by cardiogenic shock: a propensity-matched analysis - Rui Yan; Jie Yang; Bo Shi; Congyan Ye; Shizhe Fu; Kairu Wang; Ru Yan; Shaobin Jia; Xueping Ma; Guangzhi Cong (BMC Cardiovascular Disorders)
Abstract Background Mechanical circulatory support (MCS) devices have been widely used for managing acute myocardial infarction complicated by cardiogenic shock (AMI-CS). However, their use additionally elevates acute ischemic stroke (AIS) risk. There is insufficient data on the risk of AIS associated with early versus late initiation of MCS in AMI-CS cases. Therefore, this study aimed to assess the timing of MCS initiation associated with the risk of AIS in hospitalizations with AMI-CS. Methods A retrospective data analysis of the National Inpatient Sample (January 2016–December 2020) identified AMI-CS hospitalizations: categorized into early MCS initiation (< 48 h) and late MCS initiation (> 48 h). The primary outcome was AIS; the secondary outcomes included in-hospital mortality, acute kidney injury (AKI), cardiac arrest, major bleeding, and blood transfusion. The outcomes were compared using logistic multivariate regression and 1:1 propensity score matching analyses between the groups. Results Among 78,405 weighted hospitalizations with AMI-CS receiving MCS, 82.77% (n = 64,895) and 17.23% (n = 13,510) underwent early and late MCS initiation, respectively. Hospitalizations with late MCS initiation had higher risks of AIS (adjusted odds ratio [aOR], 1.46; 95%confidence interval [CI], 1.19–1.79; p < 0.001), AKI (aOR, 1.41; 95%CI, 1.27–1.55; p < 0.001), and major bleeding (aOR, 1.12; 95%CI, 1.01–1.23; p = 0.028). After propensity score matching, late MCS initiation remained associated with increased risks of AIS (aOR, 1.39; 95%CI, 1.08–1.78; p = 0.010), AKI (aOR, 1.37; 95%CI, 1.23–1.53; p < 0.001), and major bleeding (aOR, 1.14; 95%CI, 1.02–1.28; p = 0.027). Conclusions Late initiation of MCS was associated with increased risks of AIS, AKI, and major bleeding.